Azidophenyl as a click-transformable redox label of DNA suitable for electrochemical detection of DNA–protein interactions. Issue 1 (8th October 2014) - Balintová, Jana; Špaček, Jan; Pohl, Radek; Brázdová, Marie; Havran, Luděk; Fojta, Miroslav; Hocek, Michal
Abstract : A new azido-based DNA redox label which can be transformed into nitrophenyltriazole by a CuAAC click reaction was developed. It was used for the mapping of DNA–protein interactions with electrochemical detection. Abstract : New redox labelling of DNA by an azido group which can be chemically transformed to nitrophenyltriazole or silenced to phenyltriazole was developed and applied to the electrochemical detection of DNA–protein interactions. 5-(4-Azidophenyl)-2′-deoxycytidine and 7-(4-azidophenyl)-7-deaza-2′-deoxyadenosine nucleosides were prepared by aqueous-phase Suzuki cross-coupling and converted to nucleoside triphosphates (dNTPs) which served as substrates for incorporation into DNA by DNA polymerase. The azidophenyl-modified nucleotides and azidophenyl-modified DNA gave a strong signal in voltammetric studies, at −0.9 V, due to reduction of the azido function. The Cu-catalyzed click reaction of azidophenyl-modified nucleosides or azidophenyl-modified DNA with 4-nitrophenylacetylene gave nitrophenyl-substituted triazoles, exerting a reduction peak at −0.4 V under voltammetry, whereas the click reaction with phenylacetylene gave electrochemically silent phenyltriazoles. The transformation of the azidophenyl label to nitrophenyltriazole was used for electrochemical detection of DNA–protein interactions (p53 protein) since only those azidophenyl groups in the parts of the DNA not shielded by the bound p53 protein were transformed to nitrophenyltriazoles, whereas those covered by the protein were not.